Microscopic simulations of high harmonic generation from semiconductors - Trautmann, Alexander; Zuo, Ruixin; Wang, Guifang; Hannes, Wolf-Rüdiger; Yang, Shidong; Thong, Le Huu; Ngo, Cong; Steiner, Johannes; Ciappina, Marcelo; Reichelt, Matthias; Duc, Huynh Thanh; Song, Xiaohong; et al. (Ultrafast Phenomena and Nanophotonics XXVI)

Theoretical analysis of correlations between two quantum fields exciting a three-level system using the cluster-expansion approach - Rose, Hendrik; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina (Ultrafast Phenomena and Nanophotonics XXVI)

Coherent contributions to population dynamics in a semiconductor microcavity - Paul, J.; Rose, Hendrik; Swagel, E.; Meier, Torsten; Wahlstrand, J. K.; Bristow, A. D. (Physical Review B)

Super-Bloch oscillations with parametric modulation of a parabolic trap - Meier, Torsten; Ali, Usman (Condensed Matter)

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, Dirk Florian; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, Klaus; Reuter, Dirk; Schumacher, Stefan; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Helical Polariton Lasing from Topological Valleys in an Organic Crystalline Microcavity - Long, Teng; Ma, Xuekai; Ren, Jiahuan; Li, Feng; Liao, Qing; Schumacher, Stefan; Malpuech, Guillaume; Solnyshkov, Dmitry; Fu, Hongbing (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Manipulating polariton condensates by Rashba-Dresselhaus coupling at room temperature - Li, Yao; Ma, Xuekai; Zhai, Xiaokun; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

Unidirectional vortex waveguides and multistable vortex pairs in polariton condensates - Gao, Xinghui; Hu, Wei; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Switching Off a Microcavity Polariton Condensate near the Exceptional Point - Li, Yao; Ma, Xuekai; Hatzopoulos, Zaharias; Savvidis, Pavlos G.; Schumacher, Stefan; Gao, Tingge (ACS Photonics)